Agricultural service delivery: strengthening private crop protection service in southern Ethiopia. Issue 8 (16th November 2016) - Shiferaw, Abebe; Dindamo, Bereket; Lemma, Tesfaye; Hoekstra, Dirk
ABSTRACT: As one element of agricultural service delivery, in Ethiopia crop protection service has generally only involved the private sector on a small scale. This article outlines a case study where private crop protection service (PCPS) was strengthened from 2006 to 2010 in Halaba Special District, southern Ethiopia. The study used questionnaires, analysis, service comparison, ranking, and indicator-based assessments. The study shows that PCPS in 2007/08 crop seasons served 1, 104 households on 1, 707 ha of land in 19 Kebeles, contributing US327, 752 in total. Assessment indicators values were better for PCPS than the informal crop protection service. Piloting PCPS strengthening is recommended to improve crop protection service and reduce crop loss in Ethiopia.